A Defected Structure Shaped CPW-Fed Wideband Microstrip Antenna for Wireless Applications - Puneet Khanna; Amar Sharma; Kshitij Shinghal; Arun Kumar (Journal of Engineering)
A coplanar waveguide- (CPW-) fed compact wideband defected structure shaped microstrip antenna is proposed for wireless applications. Defected structure is produced by cutting the U shape antenna in the form of two-sided T shape. The proposed antenna consists of two-sided T shape strip as compared to usual monopole patch antenna for minimizing the height of the antenna. The large space around the radiator is fully utilized as the ground is on the same plane as of radiator. Microstrip line feed is used to excite the proposed antenna placed on an FR4 substrate (dielectric constant εr=4.4). The antenna is practically fabricated and simulated. Simulated results of the proposed antenna have been obtained by using Ansoft High-Frequency Structure Simulator (HFSS) software. These results are compared with measured results by using network analyzer. Measured result shows good agreement with the simulated results. It is observed that the proposed antenna shows a wideband from 2.96 GHz to 7.95 GHz with three bands at f1=3.23 GHz, f2=4.93 GHz, and f3=7.04 GHz.